Outcomes of cirrhotic patients with pre-capillary pulmonary hypertension and pulmonary vascular resistance between 2 and 3 Wood Units. Issue 2 (4th August 2022) - Certain, Marie Caroline; Baron, Audrey; Turpin, Matthieu; Ebstein, Nathan; Boucly, Athénaïs; Beurnier, Antoine; Jevnikar, Mitja; Roche, Anne; Keddache, Sophia; Bulifon, Sophie; Seferian, Andrei; Jaïs, Xavier; et al.
Portopulmonary hypertension (PoPH) is a subtype of pulmonary arterial hypertension (PAH) complicating the course of portal hypertension [1, 2]. Similar to other causes of PAH, PoPH is characterised by a progressive structural and functional remodelling of small pulmonary arteries leading to pre-capillary pulmonary hypertension defined by a mean pulmonary artery pressure (mPAP) ≥25 mmHg, normal pulmonary artery wedge pressure (PAWP) ≤15 mmHg and raised pulmonary vascular resistance (PVR) >3 Wood Units (WU) [1 ]. PoPH negatively impacts survival of patients with portal hypertension. Early detection of PoPH is of particular importance because it is treatable with PAH drugs and basic therapies such as diuretics [1, 3]. Pulmonary vascular resistance between 2 and 3 Wood Units in patients with portal hypertension and pre-capillary pulmonary hypertension could characterise early portopulmonary hypertension with clinical consequences https://bit.ly/3PEFe79